2011
DOI: 10.1021/ma200799b
|View full text |Cite
|
Sign up to set email alerts
|

Norbornenyl-Based RAFT Agents for the Preparation of Functional Polymers via Thiol–Ene Chemistry

Abstract: A synthetic platform for the preparation of various norbornenyl (Nb) containing reversible additionÀfragmentation chain transfer (RAFT) agents has been developed. The design of the chain transfer agents (CTAs) is based on the desymmetrization of R,R 0 -dibromo-p-xylene by monosubstitution with an alkoxide anion and subsequent replacement of the residual bromine atom in the benzylic bromide to create several series of RAFT CTA including trithiocarbonate, xanthate and dithiobenzoate CTAs, allowing for the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 81 publications
0
27
0
1
Order By: Relevance
“…A [285] BA [285] St [285] 54 S S * St [132,286] PFPVS [169] PVS [169] 381 [287] (382) [287] 414 [288] BA [286] 364 [289] (VAc) [274] (NVP) [248] (NES) [290] (BES) [290] MAA/EGDMA [291] (PFPVS-b-PS) [169] (399-b-EA) [288] 364-b-387 [289] 55 S S * tBA [292] 368 [292] tBA-b-368 [292] (Continued ) [293] St [293] 57 S S N * iBoA [268,[294][295][296] 351 [297] St [298] 58…”
Section: S S O Nunclassified
See 1 more Smart Citation
“…A [285] BA [285] St [285] 54 S S * St [132,286] PFPVS [169] PVS [169] 381 [287] (382) [287] 414 [288] BA [286] 364 [289] (VAc) [274] (NVP) [248] (NES) [290] (BES) [290] MAA/EGDMA [291] (PFPVS-b-PS) [169] (399-b-EA) [288] 364-b-387 [289] 55 S S * tBA [292] 368 [292] tBA-b-368 [292] (Continued ) [293] St [293] 57 S S N * iBoA [268,[294][295][296] 351 [297] St [298] 58…”
Section: S S O Nunclassified
“…A [285] VAc [285] 235 [520,521] 236 O S S A* (NES) [290] (BES) [290] (Continued ) [293] VAc [293] 238…”
Section: Pcl Macro-raft Agentmentioning
confidence: 99%
“…Cheng and coworkers46 reported a one‐pot grafting‐from synthesis of brush copolymers by combining ROMP and polymerization of amino acid N ‐carboxyanhydrides; however, when a grafting‐through method was attempted, the polymerizations were uncontrolled and led to broad MWDs. Inspired by recent studies of the direct synthesis of NB macromonomer by selective controlled radical polymerizations (RAFT and ATRP)36, 38, 47–49 and the high efficacy of ROMP of NB‐functionalized (macro)monomers by Grubbs' catalysts in the presence of methacrylate functional groups,50, 51 in this communication, we report advancement of synthetic methodologies to accomplish the facile, one‐pot tandem RAFT and ROMP, grafting‐through preparation of well‐defined brush copolymers with controllable dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Next, DNA–polymer conjugation was attempted using poly(NIPAM) end-capped with a Nb group ( P8 )52. After reacting with 10  μ M s0 - Tz DNA overnight at room temperature in DMF, DMAc or NMP (see Table 2), 15% native PAGE analysis revealed that the conjugate had been formed in up to 50% yield (by densitometry) – see Fig.…”
Section: Resultsmentioning
confidence: 99%